Educational Values in the Qur’an and Hadith as the Foundation of Character Education - Haetami, Husnul; Sulhan, Ahmad; Sa’i , Muhammad (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study explores the educational values contained in the Qur’an and Hadith as the fundamental foundation for character education in Islamic learning contexts. Amid the challenges of moral decline and the weakening of ethical awareness in contemporary society, this research aims to identify and analyze key Qur’anic and Prophetic values that contribute to the formation of holistic character development. Using a qualitative library research method with a thematic analysis approach, relevant verses of the Qur’an and selected Hadith were examined to uncover core educational principles, including integrity, responsibility, discipline, compassion, justice, and spiritual consciousness. The findings indicate that the Qur’an and Hadith present an integrative educational framework combining moral, spiritual, intellectual, and social dimensions, which supports the development of balanced and ethical individuals. These values are not only normative teachings but also provide practical guidance for educational processes rooted in exemplary conduct, habituation, dialogue, and reflective learning. The study concludes that integrating Qur’anic and Prophetic educational values into modern character education curricula is essential to strengthen moral identity and foster socially responsible learners in the contemporary era.